THE POWP- A FINANCE APP (CIPEEX, 2024)
BASED ON THE RESEARCH CONDUCTED, A SIGNIFICANT DIFFICULTY IN MANAGING THEIR FINANCES WAS OBSERVED AMONG INDIVIDUALS. IT WAS IN THIS CONTEXT THAT THE IDEA OF POWP EMERGED. POWP IS AN APPLICATION DEDICATED TO FINANCIAL CONTROL AND ORGANIZATION, WITH THE PURPOSE OF CONTRIBUTING TO IMPROVED FINANCIAL EDUCATION AND ASSISTING USERS IN EFFICIENTLY ACHIEVING THEIR FINANCIAL GOALS. FROM THE STUDIES AND INVESTIGATIONS CONDUCTED, IT WAS IDENTIFIED THAT THE PRIMARY TARGET AUDIENCE IS UNIVERSITY STUDENTS, ALTHOUGH IT IS ACCESSIBLE TO ANYONE.IN LINE WITH [1]THE FAST-PACED LIFESTYLE THAT HAS BECOME COMMON, POWP PRESENTS A PRACTICAL SOLUTION TO FACILITATE FINANCIAL CONTROL. THE APPLICATION WILL OFFER A WIDE RANGE OF FEATURES DESIGNED TO SIMPLIFY THE TRACKING OF FINANCES, INCLUDING INTEGRATION WITH CREDIT CARDS AND THE GENERATION OF DETAILED EXPENSE REPORTS.TO DETERMINE THE STRUCTURE AND OPERATION OF THE SYSTEM, THE STANDARD BPMN NOTATION WAS ADOPTED, ALLOWING FOR THE VISUAL REPRESENTATION OF WORKFLOW AND INTERACTIONS AMONG THE INVOLVED ACTIVITIES. ADDITIONALLY, THE AGILE SCRUM METHODOLOGY WAS CHOSEN DUE TO ITS EASE OF IMPLEMENTATION AND UNDERSTANDING BY THOSE INVOLVED, AS WELL AS ITS FOCUS ON INCREMENTAL DELIVERIES AND CONTINUOUS CUSTOMER INVOLVEMENT. THIS PROCESS WILL ENSURE AN EMPHASIS ON THE CONTINUOUS DELIVERY OF FUNCTIONAL REQUIREMENTS.THE DESIRED OUTCOME OF THIS PROJECT IS TO PROVIDE USERS WITH A PRACTICAL AND EFFICIENT TOOL FOR MANAGING THEIR FINANCES, HELPING THEM ACHIEVE THEIR FINANCIAL GOALS MORE EFFECTIVELY. IT IS EXPECTED THAT POWP WILL CONTRIBUTE TO USERS' FINANCIAL EDUCATION, PROMOTING A BETTER UNDERSTANDING AND MANAGEMENT OF THEIR PERSONAL FINANCES, REGARDLESS OF THEIR AGE OR PRIOR KNOWLEDGE OF THE SUBJECT.FURTHERMORE, POWP'S COMMITMENT TO SOCIAL RESPONSIBILITY WILL BE HIGHLIGHTED, WITH RESOURCES ALLOCATED TO SUPPORT FINANCIAL EDUCATION INITIATIVES AND CHARITABLE ORGANIZATIONS THAT PROMOTE FINANCIAL WELL-BEING IN DISADVANTAGED COMMUNITIES. THUS, POWP AIMS NOT ONLY TO BE A POWERFUL FINANCIAL TOOL BUT ALSO A POSITIVE FORCE IN SOCIETY, PROMOTING FINANCIAL INCLUSION AND SUSTAINABLE ECONOMIC GROWTH.&NBSP;&NBSP;